PENGARUH MODEL PEMBELAJARAN CONECTING, ORGANIZING, REFLECTING, EKTENDING (CORE) TERHADAP KEMAMPUAN PENALARAN MATEMATIS DENGAN MENGGUNAKAN MEDIA KOMUSIGA - Elmin Astuti Waruwu; Zulmi Roestika Rini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to examine the implementation of the Connecting, Organizing, Reflecting, Extending (CORE) learning model assisted by KOMUSIGA media, to identify students' mathematical reasoning ability before and after the learning process, and to analyze the effect of the CORE learning model assisted by KOMUSIGA media on the mathematical reasoning ability of third-grade students at SD Negeri Harjosari 02. This research employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of 50 students, including 25 students in the experimental class and 25 students in the control class. Data were collected through a mathematical reasoning test and a student response questionnaire. The data were analyzed using the normality test, homogeneity test, and Independent Samples t-test with IBM SPSS Statistics version 26. The findings revealed that the implementation of the CORE learning model assisted by KOMUSIGA media received a very positive response from students, as indicated by a questionnaire score of 92% in the experimental class, while the control class achieved 68%. The prerequisite tests confirmed that the data were normally distributed and homogeneous. Furthermore, the Independent Samples t-test yielded a significance value (Sig. 2-tailed) of 0.012 (<0.05), indicating a significant difference between the experimental and control groups. These findings demonstrate that the CORE learning model assisted by KOMUSIGA media has a significant positive effect on students' mathematical reasoning ability. Therefore, the CORE learning model assisted by KOMUSIGA media can be recommended as an alternative instructional approach to improve elementary school students' mathematical reasoning ability, particularly in learning plane geometry.